Maintenance of Certification: How Performance in Practice Changes Improve Tobacco Cessation in Addiction Psychiatrists’ Practice - Ford, James H. (Am J Addict, 2016)
BACKGROUND AND OBJECTIVES: In 2000, the American Board of Medical Specialties implemented the Maintenance of Certification (MOC), a structured process to help physicians identify and implement a quality improvement project to improve patient care. This study reports on findings from an MOC Performance in Practice (PIP) module designed and evaluated by addiction psychiatrists who are members of the American Academy of Addiction Psychiatry (AAAP). METHOD: A 3-phase process was utilized to recruit AAAP members to participate in the study. The current study utilized data from 154 self-selected AAAP members who evaluated the effectiveness of the MOC Tobacco Cessation PIP. RESULTS: Of the physicians participating, 76% (n 120) completed the Tobacco PIP. A paired t-test analysis revealed that reported changes in clinical measure documentation were significant across all six measures. Targeted improvement efforts focused on a single clinical measure. Results found that simple change projects designed to improve clinical practice led to substantial changes in self-reported chart documentation for the selected measure. CONCLUSIONS: The current findings suggest that addiction psychiatrists can leverage the MOC process to improve clinical care.